A focused review on the thermo-stamping process and simulation progresses of continuous fibre reinforced thermoplastic composites. (1st November 2021) - Chen, Hongda; Li, Shuxin; Wang, Jihui; Ding, Anxin
Abstract: This focused review for the development of the thermo-stamping process and simulation is concentrated on the systemically overview of the representative publications reflecting the research progress in this area rather than a comprehensive survey of the literatures directly and indirectly related to the subjects. The key features of the global process and the local process and the corresponding simulation methods are reviewed and the merit of the publications in the context of thermo-stamping is discussed. The models on how microscopic defects are created during consolidation and many other studies are out of scope. The review will highlight the development of the thermo-stamping process and considerable progress in the simulation techniques and try to identify the gaps in the current research and the challenges to be met to achieve the goal for practical engineering application of this advanced forming method.